2013
DOI: 10.1016/j.phytochem.2013.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin determination in blueberry extracts from various cultivars and their antiproliferative and apoptotic properties in B16-F10 metastatic murine melanoma cells

Abstract: Blueberry consumption is associated with health benefits contributing to a reduced risk for cardiovascular disease, diabetes and cancer. The aim of this study was to determine the anthocyanin profile of blueberry extracts and to evaluate their effects on B16-F10 metastatic melanoma murine cells. Seven blueberry cultivars cultivated in Romania were used. The blueberry extracts were purified over an Amberlite XAD-7 resin and a Sephadex LH-20 column, in order to obtain the anthocyanin rich fractions (ARF). The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 57 publications
5
95
0
5
Order By: Relevance
“…The ARF used presented a high content and great variety of anthocyanins, which is in agreement with previously reported findings from different cultivars around the world [26,38,39]. However, the anthocyanin profile was somewhat different, with malvidin as the major class, instead of cyanidin, and malvidin-3-galactoside and petunidin-3-arabinoside in the highest concentrations (Fig 1).…”
Section: Discussionsupporting
confidence: 91%
“…The ARF used presented a high content and great variety of anthocyanins, which is in agreement with previously reported findings from different cultivars around the world [26,38,39]. However, the anthocyanin profile was somewhat different, with malvidin as the major class, instead of cyanidin, and malvidin-3-galactoside and petunidin-3-arabinoside in the highest concentrations (Fig 1).…”
Section: Discussionsupporting
confidence: 91%
“…Both the dichloromethane and the methanolic extracts significantly inhibited colon, breast and blood cell cancers by suppressing cell growth and proliferation and also via inducing cell cycle arrest and apoptosis (Leardkamolkarn et al, 2011). In 2013, anthocyanins purified from blueberry extracts were found to inhibit melanoma tumor cell proliferation and induce apoptosis (Bunea et al, 2013). Kum doisaket contains several active compounds such as proanthocyanidin and cyanidin 3-glucoside.…”
Section: Discussionmentioning
confidence: 99%
“…Sudheesh et al (1997) demonstrated the beneficial, hypolipidemic effect of phenolic phytochemicals from eggplant in normal and cholesterol fed animals. Additionally, the peel of eggplant is rich in anthocyanins which play an important role in the prevention of cancer and other diseases by preventing cellular DNA damage (Bunea et al, 2013;Lim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%